2007
DOI: 10.1007/s11255-007-9209-7
|View full text |Cite
|
Sign up to set email alerts
|

Rising PSA in patients with minor LUTS without evidence of prostatic carcinoma: a missing link?

Abstract: An increased PSA in patients with minor or no LUTS, clinical BPH and negative extended multi-site prostate biopsy is strongly correlated to bladder outlet obstruction. Therefore, patients with these characteristics should be treated with TURP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…It has subsequently been shown that patients with minor or no LUTS undergoing PBx because of an elevated serum PSA and being diagnosed with benign prostate all had BOO on pressure uroflowmetry. 11 …”
Section: Introductionmentioning
confidence: 99%
“…It has subsequently been shown that patients with minor or no LUTS undergoing PBx because of an elevated serum PSA and being diagnosed with benign prostate all had BOO on pressure uroflowmetry. 11 …”
Section: Introductionmentioning
confidence: 99%
“…In our study, a suspicious PSA velocity ranging between 1.1 and 7.0 ng/ml/ year (with a mean of 3.0 ng/ml/year) was measured in 20 patients in both groups, but the subsequent biopsies were negative. This implies that, in addition to the PSA levels [3] , the PSA velocity can be a parameter for BOO. Altogether, when the PSA level is elevated or rising, and/or the PSA density is elevated and/or the PSA velocity is pathological, negative extended (multi-site) biopsies suggest the presence of BOO.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that in those patients, bladder outlet obstruction (BOO) can be the reason for elevated and/or rising PSA levels [3] . We also demonstrated that after performing a diagnostic transurethral resection of the prostate (TURP), BPH is encountered in most of these patients (90.2%) [4] .…”
Section: Introductionmentioning
confidence: 99%
“…In our series of studies [4, 7072], we included a population with very specific characteristics that are notwithstanding regularly encountered in a urological practice. Therefore, we investigated patients with elevated and/or rising PSA, minor LUTS, negative DRE and TRUS, and (multiple) negative extended prostate biopsies.…”
Section: What Has Been Suggested So Far To Deal With Those Patients?mentioning
confidence: 99%
“…More specifically, this will be the case if the patient suffers only minor LUTS. We have previously shown that this group of patients (patients with elevated/and or rising PSA levels, minor LUTS and no signs of prostate cancer) are likely to have bladder outlet obstruction (BOO) on pressure flowmetry according to Abram–Griffiths definition [3, 4]. Despite minor to no LUTS, transurethral resection of prostate (TURP) is a therapeutic option that can be offered to patients resulting in (super)normalisation of PSA levels, symptomatic benefit, and improvement of the quality of life.…”
Section: Introductionmentioning
confidence: 99%